Pathways for Urban Renewable Energy Zones Final report - Mortimer, G.; Dwyer, S.; Orbe, J.G.; Rajakaruna, Sumedha; Silva, Angie; Pashajavid, Ehsan; Amarasinghe, D. (2022)
Distributed Energy Resources (DERs) are a large and growing component of the Australian electricity network and a major factor in corporate and regional strategies for economic growth, environmental sustainability, and social wellbeing. Blessed with one of the best solar resources in the world and driven by government incentives, high electricity prices, and the declining cost of the technology, Australian householders have become world leaders in rooftop solar. Australian organisations are acting as trailblazers in converting their infrastructure to electricity-producing assets to reduce their emissions, minimise their energy bills and enhance their environmental credentials. Indeed, it is widely accepted that DERs will be a cornerstone of Australia’s energy system transition to net zero. However, a central challenge remains how we best integrate rapidly increasing levels of DER into reliable and cost-competitive energy systems. This RACE for 2030 project brought together organisations from universities, state governments, technology providers, industry experts, electricity network businesses and energy retailers to explore whether a Urban Renewable Energy Zone (UREZ) is a useful mechanism to accelerate DER investments in our cities while maximising the use of existing grid infrastructure and driving other benefits. The report synthesises the results from consultation, desktop research and network modelling completed in a six-month RACE for 2030 Fast Track Project.